2023
DOI: 10.3390/cancers15153889
|View full text |Cite
|
Sign up to set email alerts
|

The Neurodevelopmental and Molecular Landscape of Medulloblastoma Subgroups: Current Targets and the Potential for Combined Therapies

Hasan Slika,
Paolo Alimonti,
Divyaansh Raj
et al.

Abstract: Medulloblastoma is the most common malignant pediatric brain tumor and is associated with significant morbidity and mortality in the pediatric population. Despite the use of multiple therapeutic approaches consisting of surgical resection, craniospinal irradiation, and multiagent chemotherapy, the prognosis of many patients with medulloblastoma remains dismal. Additionally, the high doses of radiation and the chemotherapeutic agents used are associated with significant short- and long-term complications and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 178 publications
0
3
0
Order By: Relevance
“…Just like the other groups, Group 4 is also categorized into different subgroups with distinct genetic hallmarks. Herein, the subgroups 4α, 4β, and 4γ are characterized by MYCN amplification, SCNAIP duplication, and CDK6 amplification, respectively [ 27 ]. They all carry similar prognoses, with a 5-year survival rate of around 70–80% [ 18 ].…”
Section: The Molecular Subgroups Of Medulloblastomamentioning
confidence: 99%
See 2 more Smart Citations
“…Just like the other groups, Group 4 is also categorized into different subgroups with distinct genetic hallmarks. Herein, the subgroups 4α, 4β, and 4γ are characterized by MYCN amplification, SCNAIP duplication, and CDK6 amplification, respectively [ 27 ]. They all carry similar prognoses, with a 5-year survival rate of around 70–80% [ 18 ].…”
Section: The Molecular Subgroups Of Medulloblastomamentioning
confidence: 99%
“…In this context, Ramaswamy et al confirmed that the molecular subtype of medulloblastoma at recurrence is consistent with that of the original tumor [ 83 ]. This might be related to the fact that different molecular subtypes have different neurodevelopmental origins [ 27 ]. However, despite this lack of subtype switching, the recurrent tumors display significant divergence from the distribution of cellular states and genetic footprint of the primary tumor [ 82 ].…”
Section: Main Drivers Of Treatment Resistancementioning
confidence: 99%
See 1 more Smart Citation